2012
DOI: 10.1007/s11144-012-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water temperature on the photocatalytic activity of titanium dioxide

Abstract: In this study, it was shown that a possible explanation of increasing photocatalytic activity with temperature may be the fact that with increasing water temperature, the amount of hydroxyl radicals in water also increases, because the ionic product of water increases with an increase in temperature. For measurements of the amount of hydroxyl radicals, the fluorescence technique was used. Terephthalic acid was used as a hydroxyl radical scavenger. After inducing of TiO 2 , positive holes in the valance band ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…According to the Arrhenius equation, the heat produced by the photothermal effects can decrease the activation energy and increase the pre-exponential factor, which benefits the degradation of dye. The temperature does a positive influence, identical to the results from Janus et al [ 32 ] The RhB photocatalytic degradation rate in the blackest sample S3 was 2.4 times that of the transparent sample S4. Figure 5 c indicates that Sample S3 exhibited a larger photoelectric current than others, which rose to 15 times compared with the transparent sample S4.…”
Section: Resultssupporting
confidence: 84%
“…According to the Arrhenius equation, the heat produced by the photothermal effects can decrease the activation energy and increase the pre-exponential factor, which benefits the degradation of dye. The temperature does a positive influence, identical to the results from Janus et al [ 32 ] The RhB photocatalytic degradation rate in the blackest sample S3 was 2.4 times that of the transparent sample S4. Figure 5 c indicates that Sample S3 exhibited a larger photoelectric current than others, which rose to 15 times compared with the transparent sample S4.…”
Section: Resultssupporting
confidence: 84%
“…Thus, at a higher temperature, rotifers might ingest more nTiO 2 . Second, it has been demonstrated that high temperature increased the photocatalytic activity of nTiO 2 (Janus et al, 2012), which then induced heavier oxidative stress to rotifers.…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic environments, nanomaterials induced overproduction of ROS, which then caused lipid peroxidation and damages to cell membranes (Tee, Ong, Bay, Ho, & Leong, 2016). The photocatalytic activity of nTiO 2 on ROS production was affected by temperature (Janus, Kusiak‐Nejman, & Morawski, 2012), which might affect the toxic performance of nTiO 2 . However, the effects of temperature on nTiO 2 toxicity to organisms have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits a typical zero-order kinetic reaction character. [49][50][51] However, both light and heat can speed up the reaction rate and it is important to note that the reaction rate can be greatly improved with a slight increase in the reaction temperature. 47,48 The result observed here further conrms that the complex-route works following a different mechanism.…”
Section: Photocatalytic Mechanism Of Nb 2 O 5 With Heterojunctionsmentioning
confidence: 99%
“…In the photocatalytic reports, researchers seldom study the temperature effect. [49][50][51] However, both light and heat can speed up the reaction rate and it is important to note that the reaction rate can be greatly improved with a slight increase in the reaction temperature.…”
Section: Photocatalytic Mechanism Of Nb 2 O 5 With Heterojunctionsmentioning
confidence: 99%